Dramatisme dalam Surah ‘Abasa (80): 1-10: - Ar Ridho, Ahmed Zaranggi (SUHUF, 2024)
This article explores the logic of Husein al-Habs’yi’s dramatism in the book ‘Tafsir Surah ‘Abasa,’ which brings the discourse of surah ‘Abasa to be more inclusive. The little attention to the process of interpretation in tafsir works in the 1990s limited the diversity of Qur’anic interpretation in Indonesia. Husein al-Habsyi’s rejection of the interpretation of ‘the frowning-faced Prophet’ through an interdisciplinary approach in a reportage-scientific style is the uniqueness of his interpretation. This research uses a descriptive method with content analysis in Kenneth Burke’s dramatism frame as a data analysis tool. This study found three structures that guide the process, logic, and central message behind Husein al-Habsyi’s interpretation of surah ‘Abasa. First, the interpretation process integrates Qur’anic text and social science tools. Second, incorporating systematic tools is guided by three dramatic logics: scene-acting ratio, scene-agent, and attitude framing. Third, using interdisciplinary tools through scientific-reportage-style presentations implies three main messages: critical cultural care, scientific integration, and dissemination of ukhuwah Islamiah. These three findings enrich the presentations, methods, and motive of interpretation in Qur’anic interpretation discourses in Indonesia, especially in the 1990s.